1967
DOI: 10.21236/ad0652846
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and Pathology of Repeated Doses of Monomethylhydrazine in Monkeys.

Abstract: Organizations and individuals receiving reports via the Aerospace Medical Research Laboratories' automatic mailing lists should submit the addressograph plate stamp on the report envelope or refer to the code number when corresponding about. change of address or cancellation. Do not return this copy. Retain or destroy, The experiments reported herein were conducted according to the "Principles of Laboratory Animal Care" establishe, by the National Society for Medical Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Apparently the inactivation of B 6 vitamers is involved in its action. Back and Pinkerton 11 obtained results which may throw some light on the confused picture resulting from the observations of Hendricks 92 and Dearness S2 because they found that with Macaque monkeys the difference between a no-effect dose and a lethal dose of monomethylhydrazine is very small.…”
Section: Crc Critical Reviews In Food Technologymentioning
confidence: 99%
“…Apparently the inactivation of B 6 vitamers is involved in its action. Back and Pinkerton 11 obtained results which may throw some light on the confused picture resulting from the observations of Hendricks 92 and Dearness S2 because they found that with Macaque monkeys the difference between a no-effect dose and a lethal dose of monomethylhydrazine is very small.…”
Section: Crc Critical Reviews In Food Technologymentioning
confidence: 99%